PERFORMANCE OF LFAC TRANSMISSSION SYSTEMFOR TRANSIENTSTATE - Amol D. Chate; Ashwini Pawar; Dr. Asha Gaikwad (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with thetransientperformance of a low-frequency ac (20Hz) transmission system for a wind rampevent. The LFAC system is interconnected with the 50Hz grid with a Cycloconverter. The wind power from the offshore is in the form of dc, and is interconnected to the LFAC transmission line with a twelve-pulse thyristor inverter. Thegraphs of transient response of proposed system parametersare plotted.The circuit model of LFAC system is simulated in MATLAB/SIMULINK.